Effect of Eggshell Wastes from Different Bird Species on Growth and Yield of Peanut - Nittaya Phakamas; Phonthip Gatewit; Maythavee Kongsamret; Pornpen Somchit; Chorkaew Aninbon (My University, 2022)
Eggshell wastes from various bird species may be used as an alternative calcium source for peanut production. The purpose of this experiment was to determine the effects of eggshell waste from chicken, duck and quail on the growth and yield of peanut. Five treatments consisting of no gypsum control, three eggshell wastes from chicken, duck and quail, and commercial gypsum were laid out in completely randomized design with four replications during December 2020 to April 2021. Peanut variety KK 6 was planted in cement plots. Gypsum and eggshell wastes were applied at the rate of 312.5 kg/ha at 25 days after planting. Data were collected for growth parameters, pod yield and yield components at harvest. Analysis of variance was performed for all parameters, and means were separated by least significant difference at the 0.01 probability level. Eggshell wastes from chicken, duck and quail did not show significant effects for leaf dry weight, stem dry weight, total dry weight and 100 seed weight, but they significantly increased pod dry weight, seed yield, filled seed, shelling percentage and harvest index. All eggshell wastes produced higher growth and yield of peanut than commercial gypsum. Eggshell waste from duck seemed to be better than the other sources in terms of yield increase in KK 6 peanut.
Keywords: Dry weight; Completely randomized design; Peanut Plant Research Studies